2010
DOI: 10.1007/s00412-010-0277-6
|View full text |Cite
|
Sign up to set email alerts
|

Difference between random and imprinted X inactivation in common voles

Abstract: During early development in female mammals, most genes on one of the two X-chromosomes undergo transcriptional silencing. In the extraembryonic lineages of some eutherian species, imprinted X-inactivation of the paternal X-chromosome occurs. In the cells of the embryo proper, the choice of the future inactive X-chromosome is random. We mapped several genes on the X-chromosomes of five common vole species and compared their expression and methylation patterns in somatic and extraembryonic tissues, where random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 66 publications
(103 reference statements)
1
13
0
Order By: Relevance
“…The XX TS cell line (R1) was derived and maintained in the absence of FGF-4 and heparin, a condition that maintains the undifferentiated state of multipotent TS cells in mouse [20]. In vole extraembryonic tissues, the paternal X-chromosome is inactivated [21], [22] and the vole TS cells, like these of mice, demonstrate imprinted XCI and Xist RNA accumulation on Xi (Figure 1A) [19]. The X-chromosome of M. levis is acrocentric and has a giant block of constitutive heterochromatin consisting of two repetitive sequences: MS3 (3265 bp) and MS4 (4088 bp), which contain mobile element fragments [23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The XX TS cell line (R1) was derived and maintained in the absence of FGF-4 and heparin, a condition that maintains the undifferentiated state of multipotent TS cells in mouse [20]. In vole extraembryonic tissues, the paternal X-chromosome is inactivated [21], [22] and the vole TS cells, like these of mice, demonstrate imprinted XCI and Xist RNA accumulation on Xi (Figure 1A) [19]. The X-chromosome of M. levis is acrocentric and has a giant block of constitutive heterochromatin consisting of two repetitive sequences: MS3 (3265 bp) and MS4 (4088 bp), which contain mobile element fragments [23].…”
Section: Resultsmentioning
confidence: 99%
“…RT-PCR analysis, isolation and analysis of tumors of V1 TS cells were performed as described previously [19], [21].…”
Section: Methodsmentioning
confidence: 99%
“…One such X-linked gene that might escape X inactivation in human chorionic villi is glucose-6-phosphate dehydrogenase (125). In the extraembryonic tissues of common voles (Microtus arvalis), more genes were expressed from the supposedly inactivated X chromosome than detected in somatic tissues (127). Further studies are needed to determine whether other X-associated genes may be incompletely inactivated and thereby account for sexually dimorphic placental responses.…”
Section: Sex Chromosomes and Sexually Dimorphic Effects In The Placentamentioning
confidence: 96%
“…It has been previously demonstrated that the M. rossiaemeridionalis X chromosome is inactive in Sa006 cell culture and M. arvalis X chromosome is inactive in Sad4 cell culture [26]. Sequencing PCR products from CTCF bound fractions for both Sa006 and Sad4 cell lines detected only the Xist allele corresponded to the active X chromosome (the X chromosome of M. arvalis in Sa006 line and that of M. rossiaemeridionalis in Sad4 line) (Fig.…”
Section: Resultsmentioning
confidence: 82%